Morphological studies of two Denisiella species (Collembola, Symphypleona) with an updated identification key to Denisiella species based on males - Schulz, Hans-Jürgen (Soil Organisms, 2016)
For the first time, Scanning Electron Microscopy (SEM) techniques were used to study the morphology of the genus Denisiella. Two species were examined in detail: Denisiella bretfeldi Schulz & van Harten, 2013 and D. serroseta (Börner, 1908). An updated key for identifying Denisiella species on the basis of morphological characters of their males is presented including all presently known species world-wide, for which males have been reported.
Keywords: Denisiella; SEM-photos; key males